Avaliação da atividade e mecanismo de ação antifúngico de derivadostiazólicos sobre Cryptococcusspp - Victor Augusto Teixeira Leocadio (2023)
Cryptococcosis is an invasive mycosis distributed throughout the world. It is mainly caused by two species of encapsulated yeast: Cryptococcus neoformans and C. gattii. C. neoformans is acquired mainly through contact with bird feces (mainly pigeons), inhaling the fungus. C. gattii is more commonly associated with trees, such as eucalyptus and almond trees. The most important infection caused by these species is cryptococcal meningitis, in which the fungus crosses the blood-brain barrier and causes infections in the central nervous system. Currently, the treatment for cryptococcosis is based on amphotericin B together with flucytosine and fluconazole, but for cases of meningitis this treatment is more complex and less effective. Considering the limited number of drugs for the treatment of this meningitis and its significant clinical importance, the search for new thiazole derivatives with activity against Cryptococcus is the objective proposed here. Initially, the minimum inhibitory concentration was determined against several strains of C. gattii and C. neoformans and the toxicity for the working cell, hCMEC/D3, a strain originating from cerebral microvessels. Next, an analysis of the growth curve of the yeast in contact with the drugs revealed their fungicidal action. Next, we performed a chemical-genetic analysis with a collection of 322 strains of C. neoformans mutants for different transcription factors for an initial screening of possible genes important in the action of these derivatives. We found that strains more tolerant to derivatives had deletions of genes related to adaptation to stress and resistance to heavy metals and endoplasmic reticulum stress. With these data, we evaluated the influence caused by derivatives in strains with previous exposure to them on the production of melanin and ergosterol in addition to various cellular stress factors. This exposure decreased the production of ergosterol and melanin, in addition to promoting greater tolerance to osmotic and cell membrane stressors. Subsequently, cell transmigration assays in a blood-brain barrier model revealed that the derivatives decreased the ability of C. neoformans to cross this barrier. Finally, in vivo tests in a murine model showed an extension in the survival of animals with cryptococcosis, in addition to a decrease in the fungal load in the brain and lung. With all this, we concluded, initially, that the derivatives worked here are excellent candidates for therapy of cryptococcal and pulmonary meningitis.